Historicising the Spiritual–Political Fold in Asceticism: The Sree Narayana Gurukulam and Social Change - Cybil K.V. (My University, 2025)
Narayana guru (1856–1928), in whose name the Sree Narayana Dharma Paripalana Yogam was formed in early twentieth-century Kerala, challenged the claim that brahmins made to the exclusive possession of the wisdom and practices of the Vedic and Vedantic texts. Guru did this by preaching a variant of Upanishadic philosophy and establishing temples in which he installed the deities. Drawing mainly upon the writings of a disciple, Nataraja guru (1895–1973), this article explores the links between the spiritual and the political through a historicising perspective. © 2024 CSD.